The Effect of Organizational Culture and Leadership to The Employee’s Performance Through Motivation at PT Bank Tabungan Negara (Persero) Go Public Semarang Branch Office - Mia El Fitria; Saryadi Saryadi; Wahyu Hidayat (Universitas Diponegoro, 2014)
Scope of banking is now currently experiencing a very tight competition that marked by the emergence of new banks, so the company needs the right strategy and ability to optimize human resources in the company. Conditions of the competition requires companies to have employees that have high performance. Employees performance is influenced by various factors such as organizational culture, leadership and motivation. All three of them have an important role in improving the performance of employees. Based on existing problems in this research, there was a decrease in the employee’s performance of PT. Bank Tabungan Negara (Persero) Go Public Semarang branch office in 2011 and 2012 with (0.335%) and (0.98%). The purpose of this research was to determine the effect of organizational culture and leadership to the employee’s performance through motivation at PT. Bank Tabungan Negara (Persero) Go Public Semarang branch office.The type of this research is explanatory research. The population in this research is employees of PT. BTN (Persero) Go Public Semarang branch office and the number of sample was 136 respondents. The sampling technique is proportionate stratified random sampling. The techniques of collecting data in this research with questionnaires and interviews. The analytical method that used in this research is the correlation test, R Square, simple linear regression, multiple linear regression, t test and f test with SPSS.The results of this research show that based the path analysis, organizational culture and leadership have influence on employee performance when reinforced by the motivation or through motivation. It can be conclude if the organizational culture is stronger, if there’s stand presence of good leadership and accompanied with employees high motivation, it will improve employees performance. Recomendation for PT Bank Tabungan Negara (Persero) Go Public Semarang branch office is to enable high employees performance, then the leader should be able to regard on how the employees can be more active providing inspiration, innovation and initiative in work, as well as leaders should be able to further build employees motivation to work better, and the company should pay more attention with the suitability of bonus that provided for the employees to improve their performance even better.